If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + Z + -23 = 40 Reorder the terms: -23 + Z + 4y = 40 Solving -23 + Z + 4y = 40 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '23' to each side of the equation. -23 + Z + 23 + 4y = 40 + 23 Reorder the terms: -23 + 23 + Z + 4y = 40 + 23 Combine like terms: -23 + 23 = 0 0 + Z + 4y = 40 + 23 Z + 4y = 40 + 23 Combine like terms: 40 + 23 = 63 Z + 4y = 63 Add '-4y' to each side of the equation. Z + 4y + -4y = 63 + -4y Combine like terms: 4y + -4y = 0 Z + 0 = 63 + -4y Z = 63 + -4y Simplifying Z = 63 + -4y
| Y=50-1.5(10) | | 6y+2y-2=180 | | 8x+27x-9=7(5x+9) | | p+80=9p | | p+4=3p | | 3v+58=v+78 | | 2z=z+28 | | u+38=3u | | 3t=t+54 | | c+15=2c | | 6x^2+6x-12= | | 3t=t+32 | | 4q=q+15 | | 3m-1/4-2m-2/3=1 | | u+19=2u | | q+56=5q | | 240-1.6x=0 | | ([x^2+3]+[x-5])(6)= | | (x^2+3+x-5)(6)= | | (5v+3)(9+v)= | | 6x^3/24x^4 | | -23=45-4x | | 6g-3h= | | 3662x^5-21973x^4+52874x^3-63218x^2+37715x-8980=0 | | 20y^2+13y-15=0 | | 4x^2+28xy-18y= | | 14-7t=-56 | | 2x/3-16=-6 | | 13=y+3 | | X+49=3x-10 | | 6.0/2 | | 3x+2-15x=14y-6 |